2013
DOI: 10.1039/c2cy20481a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically active structures of SiO2-supported Au nanoparticles in low-temperature CO oxidation

Abstract: Various Au/SiO 2 catalysts have been prepared by the deposition-precipitation method followed by calcination in air or reduction in H 2 . The structures of supported Au nanoparticles were characterized in detail by XRD, TEM, XPS, in situ XANES and operando DRIFTS of CO chemisorption, and their catalytic activity in CO oxidation was evaluated. Calcined in air, the gold precursor decomposes into Au(I) species at low temperatures and further to Au(0) at elevated temperatures, forming supported Au nanoparticles mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 51 publications
4
61
1
Order By: Relevance
“…4,33,34 We previously observed that the Au 4f binding energy of Au particles below 2 nm supported on SiO 2 was higher than those of larger Au particles and bulk Au, 9 but Au particles below 2 nm supported on CeO 2 in 0.18%-Au/CeO 2 catalyst exhibit the same Au 4f binding energy as those larger Au particles in 0.97%-and 5.7%-Au/CeO 2 catalysts. The BET specific surface areas of 0.18%-, 0.97%-and 5.7%-Au/CeO 2 catalysts are 79.2, 71.6 and 75.2 m 2 /g, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…4,33,34 We previously observed that the Au 4f binding energy of Au particles below 2 nm supported on SiO 2 was higher than those of larger Au particles and bulk Au, 9 but Au particles below 2 nm supported on CeO 2 in 0.18%-Au/CeO 2 catalyst exhibit the same Au 4f binding energy as those larger Au particles in 0.97%-and 5.7%-Au/CeO 2 catalysts. The BET specific surface areas of 0.18%-, 0.97%-and 5.7%-Au/CeO 2 catalysts are 79.2, 71.6 and 75.2 m 2 /g, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…4,5 The decrease in the size of supported Au particles increases the Au-support perimeter interface length and thus enhances the catalytic activity of supported Au catalysts following the periphery reaction mechanism. [6][7][8][9] The decrease in the size of Au particles can also change their electronic structure, including the quantum size effect, and subsequently the catalytic activity. [6][7][8][9] The decrease in the size of Au particles can also change their electronic structure, including the quantum size effect, and subsequently the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] The use of silica (SiO 2 ) spheres as an oxide support in the development of catalysts has attracted a great deal of attention in recent years. [7][8][9][10][11][12][13][14][15][16][17][18] For example, Yan et al prepared Co 3 O 4 nanoparticles in SiO 2 nanocapsules and found a 100% CO conversion rate at 150°C, 7 which was much better than that observed for other Co 3 O 4 nanostructures such as nanowires with exposed reactive {111} planes. Ni@SiO 2 , Co@SiO 2 and Fe@SiO 2 yolk-shell structures were prepared by Park et al and shown to be good for steam reforming of methane with high temperature stability and recyclability.…”
Section: Introductionmentioning
confidence: 94%
“…[13][14][15][16][17][18] In tests of the use of Ag/SiO 2 and Au/SiO 2 catalysts for CO oxidation, size and thermal pretreatment were shown to be important factors.…”
Section: Introductionmentioning
confidence: 99%